Noble finding of various stressors and their perceptions among patients with type 2 Diabetes mellitus attending in Pekan Hospital - Zanudin, Nurdiyana Khalisah; May, Khin Soe; Yaacob, Norhafiza; Win, Win May (2018)
Background: Reviews have shown that depression is a major problem among type 2 diabetes mellitus (T2DM) patients. However, there is limited evidence for specific stressors to be associated with stress among T2D patients. Objectives: This study aimed to identify the main stressors among the T2DM and to investigate the perceptions of the patients towards disease. Methods: A cross-sectional study conducted at Diabetic Clinic in Pekan hospital recruited the 99 volunteers [52.5% (n=52) female, 47.5% (n=47) male] with T2DM. The patients that attend to the clinic to get routine treatment were offered to answer a set of questionnaire with the aid of the caregivers. The data collected was then analyzed by using SPSS software version 21. Results: This study found that majority of the respondents [56.57% (n= 56) from total respondents] perceived the disease they are suffering from as a burdensome to them while the minority of the respondents [19.19% (n=19) from total respondents] grasped as associated with external factor such as paranormal and environment. Overall, the main stressors found in this study are the daily activity-related stressors which are regular exercise, restriction of their favorite foods and limited food consumption with percentages of 69.7% (n= 69), 56.5% (n= 56) and 56.5% (n=56) respectively from total respondents. Conclusions: This study would benefit the patients and caregivers, team members of diabetic clinic as the T2DM patients need intensive guidance and care from the educators and caregivers. Thus, team members from diabetic clinic can develop the motivation programme to help the patients in managing diabetes-related distress.